Effective photocatalytic and antibacterial activity of ecofriendly ZnO nanoparticles synthesized using Citrus sinensis Osbeck peels - Vishnu Kumar Dwivedi; Sharda Pandey; Nidhi Singh; Saurabh Kumar; Pallavi Shukla; Aradhana Mishra; Anoop Kumar Srivastava; R.K. Shukla; Anchal Srivastava (Next Materials, 2025)
The plant-mediated synthesis of ZnO NPs is a cost-effective and ecofriendly method. Therefore, the present work is focussed on the fabrication of ZnO NPs using Citrus sinensis Osbeck (mosambi) peel extract with three different concentrations of precursor-salt. The obtained three samples have quasi-spherical-shaped ZnO NPs with crystallite size along the three major planes increasing from 27 to 42 nm with increasing concentration of precursor-salt. The bandgap energy varies between 3.196 and 3.215 eV. FTIR spectroscopy exhibited a Zn–O band close to 450 cm–1. The photoluminescence spectra with excitation wavelength 325 nm exhibits emissions owing to oxygen vacancies (VO+ and VO+2) and zinc interstitial sites. The increasing concentration of precursor-salt causes a small red shift and reduction in photoluminescence intensity. The ZnO NPs demonstrate antimicrobial activity against two tomato and citrus plant phytopathogens: Xanthomonas compestris (XC) and Pseudomonas syringae (PS). The sample Z13 with concentration of 50 mg/mL i) in ethanol displayed maximum inhibition against XC without sonication and ii) in methanol displayed maximum inhibition against PS with sonication. The photocatalytic activity for methylene blue (MB) dye in an aqueous solution under ultra violet (UV) light irradiation has been studied. One of the NPs samples exhibited excellent photocatalytic activity 97.5 % dye removal in 60 min with rate constant 22.9 × 10−3 min−1 and half-life 24.9 min at pH-7. The properties of ZnO NPs signify their usage in energy harvesting, LEDs and displays also.